2004
DOI: 10.5194/acp-4-715-2004
|View full text |Cite
|
Sign up to set email alerts
|

Cloud chemistry at the Puy de Dôme: variability and relationships with environmental factors

Abstract: Abstract. The chemical composition of cloud water was investigated during the winter-spring months of 2001 and 2002 at the Puy de Dôme station (1465 m above sea level, 45 • 46 22 N, 2 • 57 43 E) in an effort to characterize clouds in the continental free troposphere. Cloud droplets were sampled with single-stage cloud collectors (cut-off diameter approximately 7 µm) and analyzed for inorganic and organic ions, as well as total dissolved organic carbon. Results show a very large variability in chemical composit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
87
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(96 citation statements)
references
References 64 publications
8
87
0
1
Order By: Relevance
“…It should be realized, however, that (S/V) and total electrolyte concentrations of typical cloud and fog droplets and, hence, g will display wide variability over daily and weekly periods. 97 Thus, by adopting a representative average value for the uptake coefficient of NO 2 (g) on tropospheric aerosols: g $ 3 Â 10 À4 (see above), we estimate k d $ 6 Â 10 À5 s À1 , which corresponds to $20% NO 2 (g) hourly conversions in clear-day conditions, i.e., in the range of those observed in the eld. 26 By assuming that all HONO produced in reaction R1 is rapidly photolyzed via R6, the rate of _OH production at the terminus of this route, r +OH (R1), will therefore be given by eqn (E3):…”
Section: How R1 Buffers Tropospheric Oh-radicalsmentioning
confidence: 99%
“…It should be realized, however, that (S/V) and total electrolyte concentrations of typical cloud and fog droplets and, hence, g will display wide variability over daily and weekly periods. 97 Thus, by adopting a representative average value for the uptake coefficient of NO 2 (g) on tropospheric aerosols: g $ 3 Â 10 À4 (see above), we estimate k d $ 6 Â 10 À5 s À1 , which corresponds to $20% NO 2 (g) hourly conversions in clear-day conditions, i.e., in the range of those observed in the eld. 26 By assuming that all HONO produced in reaction R1 is rapidly photolyzed via R6, the rate of _OH production at the terminus of this route, r +OH (R1), will therefore be given by eqn (E3):…”
Section: How R1 Buffers Tropospheric Oh-radicalsmentioning
confidence: 99%
“…The pH of the solutions has been selected to evaluate their impacts on the efficiency of bacterial INA (Attard et al, 2012). The anthropogenic activities can lead the cloud water to be pH 3.0 (Marinoni et al, 2004), which may require hundred times of the aforementioned normal concentrations of different solutions. Therefore, the concentrations of the solutions for the experiments of bacterial IN are normally set to be much higher than those of the in-situ observations (Attard et al, 2012).…”
Section: Mixture Of Bacteria and Pollutantsmentioning
confidence: 99%
“…Their results indicated that acidic pH has strong effects on the INA of Pseudomonus syringae, which can be highly reduced at the temperatures above -8°C. The anthropogenic activities can even result in the cloud water to be pH 3.0 (database available at http://www.obs.univbpclermont.fr/SO/beam/data.php), which is mainly attributed to ammonium sulfate, monocarboxylic acids (MCAs) and dicarboxylic acids (DCAs) (Marinoni et al, 2004). As dominant species of MCAs, formic and acetic acids have been found in the gas phase, aerosols cloud droplets and raindrops (Sun and Ariya, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…• C. A primary candidate is HNO 3 that was found at elevated concentrations in both clouds and aerosols on the Puy de Dôme (Marinoni et al 2004;Sellegri et al 2003). Nitric acid is very volatile and is often found attached to the particle surface.…”
Section: Case Study 4: Thermo-desorption Suppresses Onementioning
confidence: 99%